2013
DOI: 10.1080/00207721.2012.761461
|View full text |Cite
|
Sign up to set email alerts
|

An order-picking operations system for managing the batching activities in a warehouse

Abstract: Nowadays, customer orders with high product variety in small quantities are often received and requested for timely delivery. However, the order-picking process is a labour-intensive and costly activity to handle those small orders separately. In such cases, small orders are often grouped into batches so that two or more orders can be served at once to increase the picking efficiency and thus reduce the travel distance. In this paper, an order-picking operations system (OPOS) is proposed to assist the formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
0
35
0
1
Order By: Relevance
“…Other meta-heuristics applied to the OBP use clustering based on pattern of demand instead of distances covered (Ho & Tseng, 2006;Chen & Wu, 2005;Arora et al, 2017). present several heuristics for the OBP while Lam et al (2014) state the OBP as an integer programming problem in which the distances covered in each sequence of visits is estimated and the problem is solved by a heuristic based on fuzzy logic. Tsai et al (2008) use a multiple genetic algorithm to solve the OBP/OPP.…”
Section: The Problem and Literature Reviewmentioning
confidence: 99%
“…Other meta-heuristics applied to the OBP use clustering based on pattern of demand instead of distances covered (Ho & Tseng, 2006;Chen & Wu, 2005;Arora et al, 2017). present several heuristics for the OBP while Lam et al (2014) state the OBP as an integer programming problem in which the distances covered in each sequence of visits is estimated and the problem is solved by a heuristic based on fuzzy logic. Tsai et al (2008) use a multiple genetic algorithm to solve the OBP/OPP.…”
Section: The Problem and Literature Reviewmentioning
confidence: 99%
“…, f K }. The total product retrieving effort is defined as f m f r pre (1) where m fr refers to the number of forklifts required for retrieving. We denote W as warehouse storage capacity.…”
Section: Assigning the Storage Locationmentioning
confidence: 99%
“…To survive in the increasingly competitive environment of global market, logisticians have more focused and emphasized on their strategic goals to achieve shorter order cycle time, lower costs, and better customer services. 1 Therefore, the fulfilment of customers' demands with good quality products, timely product delivery, and better logistics service become vital and even the key to achieving better overall performance of enterprises. In a supply chain, warehouse is a crucial component for linking the upstream (production) and downstream (distribution) partners.…”
Section: Introductionmentioning
confidence: 99%
“…Karaenke et al [15] employed the available maximizing cardinal utility framework to a retail logistics problem whose outcomes provide the randomized matching mechanisms with an effective tool to reduce waiting times at warehouses. Lam et al [16] suggested an operation system of order picking to assist devising a plan of order picking and batch handling sequence. Matthews Visagie [17] dealt with the problem of minimizing pickers' travel distance to pick all orders in this system, which employed a relaxation of this IP formulation to find a lower bound of an optimal solution.…”
Section: Introductionmentioning
confidence: 99%